Late Cenozoic climate and the phylogenetic structure of regional conifer floras world‐wide - Eiserhardt, Wolf L; Borchsenius, Finn; Sandel, Brody; Kissling, W. Daniel; Svenning, Jens‐Christian (Global ecology and biogeography, 2015)
AIM: Using conifers as a model system, we aim to test four hypotheses. H1: the processes that shape the phylogenetic structure of regional species assemblages depend on climate. H2: apparent effects of current climate can be equally well explained by past climate. H3: strong Quaternary climate oscillations have led to phylogenetically non‐random assemblages, either with few closely related species because isolated populations do not persist long enough to become new species or with many close relatives due to increased allopatric speciation. H4: strong late Cenozoic aridification has led to assemblages with many close relatives due to extinction and adaptive radiation. LOCATION: Global. METHODS: We used boosted regression trees to relate the net relatedness index (NRI) of regional conifer assemblages to current climate, past climate (0.021, 3 and 7.3–11.6 Ma), and gradual and cyclic late Cenozoic climate change while simultaneously accounting for habitat and biogeographic covariates. RESULTS: Climate was the most important predictor of NRI, supporting H1. Current and past climate showed similar relationships with NRI, supporting H2. Conifer NRI was further related to Quaternary climate oscillations and gradual late Cenozoic climate trends, but the shape of the relationships supported neither H3 nor H4. MAIN CONCLUSIONS: The climate–NRI relationships suggest that late Cenozoic climate consistently influenced the dynamics of conifer speciation, extinction and dispersal, leading to global patterns of phylogenetic assemblage structure. We deduce from the phylogenetic structure that diversification has been highest in warm or dry climates over the last ≥11.6 Myr. The fact that phylogenetic structure is related to climate trends and oscillations indicates that climate change plays an important role in addition to climate per se, but the exact underlying mechanisms remain unclear. Our results suggest that past climate needs to be taken into account when aiming to explain the phylogenetic structure of regional assemblages and other related aspects of biodiversity.